2016
DOI: 10.1016/j.biopsych.2015.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Structural Plasticity of the Hippocampus and Amygdala Induced by Electroconvulsive Therapy in Major Depression

Abstract: Background Electroconvulsive therapy (ECT) elicits a rapid and robust clinical response in patients with refractory depression. Neuroimaging measures of structural plasticity relating to and predictive of ECT response may point to the mechanisms underlying rapid antidepressant effects and establish biomarkers to inform other treatments. Here, we determine the effects of 1) diagnosis and 2) ECT on global and local variations of hippocampal and amygdalar structure in major depression and predictors of ECT-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
214
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(243 citation statements)
references
References 75 publications
21
214
7
1
Order By: Relevance
“…This is in line with previous studies (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Bouckaert et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Sartorius et al, 2016). Only two studies found an association between hippocampal volume increase and therapeutic efficacy (Dukart et al, 2014;Joshi et al, 2015). Our data suggest that the hippocampal volume increase after ECT is transient and reverts to baseline within 6 months, even though the antidepressant effect is sustained.…”
Section: Relationship Between Depressive Symptomatology and Hippocampsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with previous studies (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Bouckaert et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Sartorius et al, 2016). Only two studies found an association between hippocampal volume increase and therapeutic efficacy (Dukart et al, 2014;Joshi et al, 2015). Our data suggest that the hippocampal volume increase after ECT is transient and reverts to baseline within 6 months, even though the antidepressant effect is sustained.…”
Section: Relationship Between Depressive Symptomatology and Hippocampsupporting
confidence: 93%
“…Several recent magnetic resonance imaging (MRI) studies have described hippocampal volume changes following ECT (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Joshi et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Bouckaert et al, 2015;Sartorius et al, 2016). Some of these studies have also addressed structural changes in other brain areas relevant to depressive disorders, such as dorsolateral prefrontal cortex, orbitofrontal cortex (Jorgensen et al, 2015), lateral temporal cortex (Bouckaert et al, 2015), caudate nucleus (Bouckaert et al, 2015), and amygdala (Tendolkar et al, 2013;Jorgensen et al, 2015;Joshi et al, 2015;Ota et al, 2015;Sartorius et al, 2016). Only one study did not detect gray matter volume changes (Nickl-Jockschat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Others (Liu et al, 2009) have also reported increased subventricular zone neuroblast cell proliferation to striatal areas following seizures. Further, ECT-related structural neuroplasticity is shown in the amygdala (Tendolkar et al, 2013;Joshi et al, 2015). These subcortical limbic structures are intricately connected to the striatum, and via the cortico-striatal-pallido-thalamo-cortical loop and projections to the hypothalamus and brainstem, act together to influence emotional expression and motivation (Cardinal et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We and other groups have shown that ECT elicits increases in hippocampal (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Joshi et al, 2015) and amygdala volume (Tendolkar et al, 2013;Joshi et al, 2015). However, whether structural plasticity occurs in the dorsal or ventral striatum/pallidum in association with treatment and illness recovery remains unknown.…”
Section: Introductionmentioning
confidence: 95%
“…With regard to the effects of interventions, it was elucidated earlier that conventional antidepressant drugs produce a normalization of the structural plasticity of the hippocampus, by altering the volume of the area, the number of cells (for example through decreasing apoptosis or inducing cellular genesis), the volume of the cells and inducing morphological changes of the dendrites and axons (Boldrini et al, 2012;Joshi et al, 2015). In the present work, we found evidence for the hypothesis that ketamine rapidly alters the volume of the CA1.SR and GCL areas (within 24 h) in the depressed animals.…”
Section: Discussionmentioning
confidence: 99%